2019
DOI: 10.1681/asn.2018121274
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Autonomous Hedgehog Signaling Is Not Required for Cyst Formation in Autosomal Dominant Polycystic Kidney Disease

Abstract: BackgroundPKD1 or PKD2, the two main causal genes for autosomal dominant polycystic kidney disease (ADPKD), encode the multipass transmembrane proteins polycystin-1 (PC1) and polycystin-2 (PC2), respectively. Polycystins localize to the primary cilium, an organelle essential for cell signaling, including signal transduction of the Hedgehog pathway. Mutations in ciliary genes that build and maintain the cilium also cause renal cystic disease through unknown pathways. Although recent studies have found alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Although HYLS1 deficiency interrupted Gpr161 trafficking out of cilia, it did not affect polycystin-2, another ciliary membrane protein mutated in polycystic kidney disease (PKD). This is consistent with the lack of renal cysts in HLS1 fetuses ( 8 ) and the recent finding that cell-autonomous Hh signaling is dispensable for renal cyst progression in PKD mouse models ( 42 ).…”
Section: Discussionsupporting
confidence: 91%
“…Although HYLS1 deficiency interrupted Gpr161 trafficking out of cilia, it did not affect polycystin-2, another ciliary membrane protein mutated in polycystic kidney disease (PKD). This is consistent with the lack of renal cysts in HLS1 fetuses ( 8 ) and the recent finding that cell-autonomous Hh signaling is dispensable for renal cyst progression in PKD mouse models ( 42 ).…”
Section: Discussionsupporting
confidence: 91%
“…In vitro analysis suggested that down-regulation of TTC30B had an inhibitory effect on Shh-pathway stimulation, consistent with our findings that Ttc30a has a role in limb patterning. Hh signaling does not influence cystogenesis in autosomal polycystic kidney disease, suggesting that other ciliary mechanisms are more likely to be at play ( 123 ). Further investigation will need to elucidate which signals are disrupted by loss of Ttc30a in renal cyst formation and which other molecular signals are affected by disrupted posttranslational tubulin modifications and defective ciliary compartmentalization.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro analysis suggested that downregulation of TTC30B had an inhibitory effect on Shh-pathway stimulation, consistent with our findings that Ttc30a has a role in limb patterning. Hedgehog signalling does not influence cystogenesis in autosomal polycystic kidney disease (ADPKD), suggesting that other ciliary mechanisms are more likely to be at play 118 . Further investigation will need to elucidate, which signals are disrupted by loss of Ttc30a in renal cyst formation and to what degree polyglutamylation and - glycylation are more widely implicated in nephronophthisis and other ciliopathies.…”
Section: Discussionmentioning
confidence: 99%